Pengembangan Bahan Ajar dengan Pendekatan Culturally Responsive Teaching pada Elemen Bilangan Kelas IV SD - Zahyuni, Violita; Nuraini, Nuraini (Jurnal Tonggak Pendidikan Dasar : Jurnal Kajian Teori dan Hasil Pendidikan Dasar, 2025)
The research conducted aims to develop printed teaching materials in the form of books with the Culturally Responsive Teaching approach in mathematics learning for grade IV of Elementary School. This research is a type of development research (Research and Development) which is a research using a qualitative and quantitative approach (mix method). The development model used in this research is the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). Data collection in this study is observation, interviews and documentation. The data analysis process uses quantitative and qualitative descriptive analysis. The development of learning materials using the Culturally Responsive Teaching Approach quantitatively and qualitatively can be said to be suitable for use in learning. The results of this study show that the validation test from material experts got an average score of 85.41% (very valid), the assessment of media experts got an average score of 90% (very valid), and for language validation got an average score of 80.55% (quite valid). The assessment of the teacher's response got an average score of 95% (very practical), and the assessment of the student's response in the large group trial got an average score of 86.25% (very practical). Referring to the results of the research on the development of teaching materials with the Culturally Responsive Teaching approach on the number elements of grade IV elementary school as a whole, it can be.